Ficus deltoidea: Effects of solvent polarity on antioxidant and anti-proliferative activities in breast and colon cancer cells - Abolmaesoomi, Mitra; Aziz, Azlina Abdul; Junit, Sarni Mat; Ali, Johari Mohd (Elsevier, 2019)
Introduction: Ficus deltoiea (FD) is traditionally used to treat hyperlipidaemia, hypertension and diabetes. Limited studies are available on their anti-proliferative effects. The aim of this study was to evaluate the antioxidant activities of the hexane, ethyl acetate, methanol and water extracts of three varieties of FD and to evaluate their anti-proliferative effects on breast and colon cancer cells. Methods: The plant extracts were analysed for polyphenolic and flavonoid content. Antioxidant activities were determined using DPPH, ABTS and O2 ·− radical scavenging assays, FRAP, Fe2+ chelating, and cellular antioxidant assays. The anti-proliferative activity and apoptotic effects of the extracts was analysed using breast (MCF-7, MDA-MB 231, HCC 1937) and colon cancer (HCT 116) cell lines. Gene expression analysis of selected extracts was investigated against HCT 116 cells. Results: Methanol was the best solvent for extraction of antioxidants and had the highest polyphenolic content (70–100 mg GAE/g), FRAP (6.0–9.0 mmol Fe2+/g), ABTS (2.0–3.0 mmol TE/g) and DPPH (EC50:200-410 μg/mL) activities. The ethyl acetate extracts of FD variety A (FDA-EA) and B (FDB-EA) demonstrated anti-proliferative activities in MCF-7, MDA-MB 231, and HCT 116 (IC50<100 μg/mL) and moderate activities in HCC 1937 (IC50:150-200 μg/mL) cells. The extracts also increased caspase 3/7 activities in HCT 116 and HCC 1937 cells. HCT 116 cells treated with FDA-EA showed upregulation of Fas1, Bax, Cdk-1, TNF-α and Cdk-2 and downregulation of Bcl-2 and Tp53 genes, implying the induction of apoptosis. Conclusion: FD especially FDA-EA is a promising source of antioxidants and anti-proliferative agents, especially against colon cancer. © 2019 Elsevier GmbH